Assessment of the Working Ability of Persons with Disabilities and Reduced Work Capacity - Balázs-Földi, Emese (International Journal of Engineering and Management Sciences, 2020)
Employment of persons with disabilities and reduced work capacity falls significantly behind that of non-disabled persons both in our country and the European Union. According to research findings, the low employment rate is partly due to discriminatory attitudes towards the group of employees concerned. In the labour market integration, apart from the attitudes of the employers, the approach of the employees working for the institute has also got a significant role, as they are the ones who as colleagues work together with persons with disabilities and reduced work capacity day by day. The research findings presented in this study focus on the research question whether the 747 employees who participated in the questionnaire survey make a distinction between persons with disabilities and persons with reduced work capacity on the grounds of their ability to work. If so, what kind of differences are noticeable and what factors have a positive impact on their approach? What is characteristic of the employees with higher level of inclusive attitudes?